2019
DOI: 10.5539/ies.v12n5p35
|View full text |Cite
|
Sign up to set email alerts
|

School Engagement for Avoiding Dropout in Middle School Education

Abstract: School engagement is a key factor in maintaining school attendance and in diminishing dropout rates. In this study, four dimensions that compose school engagement—cognitive, affective, behavioral, and agentic—were evaluated with a self-report questionnaire (Veiga, 2013), and comparisons between rural and urban schools were made. A total of 802 seventh-graders (51.2% boys and 48.8% girls), the majority of the studied children were between the ages of 12 and 13 (71.7%), attending public schools in Colombia, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…Take students in the context of education as an example. Because instruction in most classrooms is relatively dominated by teachers, many secondary and tertiary students are not comfortable with being agentically engaged and activate it more rarely than other forms of engagement (e.g., Cook-Sather et al, 2021;Manzuoli et al, 2019;Zambrano et al, 2022). Qualitative research with students and teachers reveals PATALL that agentic engagement is relatively rare for a number of reasons, including students' personalities, existing beliefs and motivation, academic and behavioral background, social roles, and especially, teachers' encouragement or discouragement of agentic engagement with their strategies and in communication (e.g., Montenegro, 2019;Zambrano et al, 2022Zambrano et al, , 2023.…”
Section: Challenges and Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Take students in the context of education as an example. Because instruction in most classrooms is relatively dominated by teachers, many secondary and tertiary students are not comfortable with being agentically engaged and activate it more rarely than other forms of engagement (e.g., Cook-Sather et al, 2021;Manzuoli et al, 2019;Zambrano et al, 2022). Qualitative research with students and teachers reveals PATALL that agentic engagement is relatively rare for a number of reasons, including students' personalities, existing beliefs and motivation, academic and behavioral background, social roles, and especially, teachers' encouragement or discouragement of agentic engagement with their strategies and in communication (e.g., Montenegro, 2019;Zambrano et al, 2022Zambrano et al, , 2023.…”
Section: Challenges and Considerationsmentioning
confidence: 99%
“…Qualitative and observational evidence also supports the validity of the agentic engagement construct (e.g., Montenegro, 2019; Zambrano et al, 2022, 2023). For example, focus groups and interviews with racially diverse high school students in urban U.S. schools have revealed that, across gender and race, students recognize the agentic engagement construct in a variety of behaviors that they or their classmates use, though rarely (e.g., Manzuoli et al, 2019), and believe it to have multiple important purposes, including to elicit motivation and learning support from teachers, to support one’s own motivational experience, and to help create a more supportive classroom environment for the entire community of learners (Zambrano et al, 2022). Focus groups with teachers have similarly revealed that they too recognize the importance of agentic engagement strategies for supporting student learning and teacher planning but feel students rarely enact them (Zambrano et al, 2023).…”
Section: Evidence On Conceptual and Predictive Validity Of Agentic En...mentioning
confidence: 99%
“…Por otra parte, se ha establecido que el clima educacional generado por la familia y la propia escuela se encuentra estrechamente vinculado con la probabilidad de permanecer en la escuela (Antelm, Gil y Cacheiro, 2015;Espinoza et al, 2016;López, Carvajal y Urrea, et al, 2013;Peña, Soto y Calderón, 2016;Salinas et al, 2017). La segunda categoría corresponde a la de los factores intraescolares que, como detonantes del fracaso y el abandono temprano, incluyen variables tales como el autoritarismo docente, los problemas de comportamiento, el bajo rendimiento académico y el adultocentrismo (Darling y Cook, 2018;Espinoza et al, 2014;Hennig, Pineda y Vargas, 2019;Rumberger y Lim, 2008). Algunos estudios han sostenido que las condiciones que gatillan el fracaso escolar son creadas por los mismos establecimientos educativos.…”
Section: Marcos Interpretativos Para Comprender El Fracaso Y La Deserción Escolarunclassified
“…Recent studies conducted in elementary or secondary school (e.g., Engels et al, 2016;Lee, 2012;Manzuoli, Pineda-B aez, & Vargas S anchez, 2019;Nicholson & Putwain, 2020) considered student engagement to be a multidimensional construct consisting of emotional, cognitive, and behavioural dimensions (Fredricks, Blumenfeld, & Paris, 2004). In higher education, student engagement is considered crucial to achieving positive academic outcomes through students' bonds with their university (Bowden, 2009;Connell & Wellborn, 1991;Sung & Yang, 2008).…”
Section: Student Engagementmentioning
confidence: 99%